The validity of breath collection bags method in detecting Helicobacter pylori using the novel BreathID®Hp Lab System: a multicenter clinical study in 257 subjects. (May 2019) - Richter, Vered; Gonzalez, Jeff O.; Hazan, Sabine; Gottlieb, Gary; Friedenberg, Keith; Gatof, David; Ganeshappa, Ravi; Delgado, Jorge-Shmuel; Abramowitz, Dov; Hardi, Robert; Coates, Allan; Haq, Mahmudul; et al.
Background and Aim: The BreathID ® Hp urea breath test provides several advantages over other 13 C breath analyzers for the detection of Helicobacter pylori . We evaluated the sensitivity and specificity of a new BreathID ® Hp Lab System (Exalenz Bioscience Ltd, Israel), a 13 C-urea breath test system using breath sampling bags that facilitates multiple testing in a multicenter international clinical study. Methods: A total of 257 subjects with evaluable results for urea breath test, rapid urease test, and histology were enrolled into two study groups: 189 naïve subjects were included in the pre-therapy group, and 68 subjects comprised the post-eradication therapy group. Analytical studies were conducted to evaluate the stability, reproducibility, and repeatability of the 13 C-urea breath test results using a delta over baseline cut-off value of 5. Results: Among the pre-therapy subjects evaluated with the composite results from the rapid urease test and histology/immunohistochemistry, 176 results matched those of the urea breath test, resulting in an overall agreement of 98.3% with a sensitivity of 100% and specificity of 97.9%. In the post-eradication therapy cohort, the overall agreement between the urea breath test and the biopsy diagnosis was 98.5%; the sensitivity of the urea breath test in this cohort was 92.3% and the specificity was 100%. There was uniformly high overall reproducibility (99.48%) of the test results over different batches of breath sample bags, when analyzed on different days and under different storage conditions, showing stability of the breath samples in the breath collection bags Conclusion: The BreathID ® Hp Lab System is a highly accurate and dependable method for the diagnosis of H. pylori infection.